The Co-Transplantation of Bone Marrow Derived Mesenchymal Stem Cells Reduced Inflammation in Intramuscular Islet Transplantation - Yoshimatsu, Gumpei (PLoS One, 2015)
AIMS/HYPOTHESIS: Although the muscle is one of the preferable transplant sites in islet transplantation, its transplant efficacy is poor. Here we attempted to determine whether an intramuscular co-transplantation of mesenchymal stem cells (MSCs) could improve the outcome. METHODS: We co-cultured murine islets with MSCs and then analyzed the morphological changes, viability, insulin-releasing function (represented by the stimulation index), and gene expression of the islets. We also transplanted 500 islets intramuscularly with or without 5 × 10(5) MSCs to diabetic mice and measured their blood glucose level, the glucose changes in an intraperitoneal glucose tolerance test, and the plasma IL-6 level. Inflammation, apoptosis, and neovascularization in the transplantation site were evaluated histologically. RESULTS: The destruction of islets tended to be prevented by co-culture with MSCs. The stimulation index was significantly higher in islets co-cultured with MSCs (1.78 ± 0.59 vs. 7.08 ± 2.53; p = 0.0025). In terms of gene expression, Sult1c2, Gstm1, and Rab37 were significantly upregulated in islets co-cultured with MSCs. Although MSCs were effective in the in vitro assays, they were only partially effective in facilitating intramuscular islet transplantation. Co-transplanted MSCs prevented an early inflammatory reaction from the islets (plasma IL-6; p = 0.0002, neutrophil infiltration; p = 0.016 inflammatory area; p = 0.021), but could not promote neovascularization in the muscle, resulting in the failure of many intramuscular transplanted islets to engraft. CONCLUSIONS: In conclusion, co-culturing and co-transplanting MSCs is potentially useful in islet transplantation, especially in terms of anti-inflammation, but further augmentation for an anti-apoptosis effect and neovascularization is necessary.